POROUS COLLAGEN SCAFFOLDS FOR BONE REGENERATION - PASCA, Roxana-Diana; TOMOAIA, Gheorghe; MOCANU, Aurora; PETEAN, Ioan; PALTINEAN, Alexandra-Gertrud; SORITAU, Olga; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2015)
This work presents an innovative procedure to fabricate collagen (COLL) structures with controlled porosity using Langmuir technique of building the self-assembled collagen structures, alone or in the presence of the cross-linker APTES [(3-aminopropyl) triethoxy silane], at the interface between air and aqueous saline subphase. Then, at selected surface pressures, the COLL structures were transferred from the interface on solid substrate (glass or mica) by Langmuir-Blodgett (LB) technique, finally obtaining porous COLL scaffolds. The morphology and porosity of COLL scaffolds were characterized by atomic force microscopy (AFM). The porous COLL structures are densified progressively at higher silane concentrations and/or at higher surface pressures. Collagen scaffolds have high potential for use in bone regeneration and tissue engineering.